GENERAL CHARACTERISTIC OF THE CRIMINAL OFFENSE «FORCING TO MARRIAGE» - Lykhova, Sofiia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: in the article the complex analysis of structure of the criminal offense provided by Art. 151-2 of the Criminal Code, taking into account the provisions of the theory of criminal, family, international law and criminological aspects. Methods: comparative legal analysis, cognitive-analytical and others. Results: given the comprehensive analysis of the issue, the paper analyses both the composition of the criminal offense in the form of coercion into marriage, and analyses some important issues of discussion. In particular, attention is paid to the situation when a person moved to Ukraine, one of whom was forced to marry, and the requirements for the invalidity of marriage under Ukrainian law were violated (for example, the wife is now 14 years old, she is her husband’s third wife and marriage taken only in a religious institution). Discussion: the question of whether a person who is formally married can be forced to marry is also analysed. An analysis of the qualification of this criminal offense in cases where coercion to cohabitation is combined with the presence of all their relationships, in particular with a person under 14 years of age. In addition, the article proves that the direct object of this criminal offense is the will of the person. In this case, the object in the following cases is non-compliance with the free and masculine values of the person. The victim of this crime can be any individual, regardless of age and condition. From an objective point of view, this crime consists in forcing the victim to commit the acts specified in the article. Coercion should be understood as influencing another person in order to achieve appropriate behaviour in the form of action or inaction, and includes five forms. The subject of a criminal offense is a general, it is a natural sane person who has reached 16 years of age at the time of the crime. From a subjective point of view, a criminal offense can only be committed intentionally. In this case, the purpose of motivating a person to move to the territory of a state other than the one in which he resides is forced to qualify only to force him or her to marry.